2017
DOI: 10.1002/1878-0261.12073
|View full text |Cite
|
Sign up to set email alerts
|

Stromal SPOCK1 supports invasive pancreatic cancer growth

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is marked by an abundant stromal deposition. This stroma is suspected to harbor both tumor‐promoting and tumor‐suppressing properties. This is underscored by the disappointing results of stroma targeting in clinical studies. Given the complexity of tumor–stroma interaction in PDAC, there is a need to identify the stromal proteins that are predominantly tumor‐promoting. One possible candidate is SPOCK1 that we previously identified in a screening effort in PDAC. We extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…This structural rearrangement is operated by remodeling enzymes belonging to MMP and LOX families, variably released either by stromal (CAF above all) or tumor cells, and results in an increased stiffening of the ECM. 100,101 Moreover, the secreted protein acidic and rich in cysteine (SPARC) family members influence deposition, aggregation, and folding of collagen fibers, even at the level of the BM. SPARC are highly conserved matricellular proteins (also called osteonectin), which possess a strong affinity for collagens, in particular for collagen-IV, that bind in a Ca 2þ -dependent manner.…”
Section: Perlecanmentioning
confidence: 99%
See 1 more Smart Citation
“…This structural rearrangement is operated by remodeling enzymes belonging to MMP and LOX families, variably released either by stromal (CAF above all) or tumor cells, and results in an increased stiffening of the ECM. 100,101 Moreover, the secreted protein acidic and rich in cysteine (SPARC) family members influence deposition, aggregation, and folding of collagen fibers, even at the level of the BM. SPARC are highly conserved matricellular proteins (also called osteonectin), which possess a strong affinity for collagens, in particular for collagen-IV, that bind in a Ca 2þ -dependent manner.…”
Section: Perlecanmentioning
confidence: 99%
“…Stimulated by TGFβ1 produced by tumor epithelial cells, SPOCK1 is expressed predominantly in the stromal fraction, and acts by modifying the collagen fiber arrangement, to favor the invasive growth of tumor cells, as shown in organotypic cocultures. 101 These structural changes involving multiple components of the ECM result in a solid framework, which exerts several promalignant effects that have been mostly elucidated by studies performed in epithelial cancers with abundant stroma akin to CCA, and will be discussed below. In this context, it is worth mentioning that while the profound changes in ECM composition between normal and diseased livers have been well described and characterized, 103 very few studies investigating the differences in ECM in premalignant biliary conditions, such as PSC and CHF/Caroli's disease, compared with diseases without predisposition to develop CCA, as PBC, cystic fibrosis-related cholangiopathy or biliary atresia, are available so far.…”
Section: Perlecanmentioning
confidence: 99%
“…SPOCK1 is an essential driver in several human cancers, [4][5][6][7][8][9][10][11] and some studies have shown that SPOCK1 is critical for DNA repair, cell cycle regulation, metastasis, and apoptosis. The oncogene sparc/ osteonectin, cwcv, and kazal-like domains proteoglycan 1 (SPOCK1) is a member of the Ca 2+ -binding proteoglycan family.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogene sparc/ osteonectin, cwcv, and kazal-like domains proteoglycan 1 (SPOCK1) is a member of the Ca 2+ -binding proteoglycan family. SPOCK1 is an essential driver in several human cancers, [4][5][6][7][8][9][10][11] and some studies have shown that SPOCK1 is critical for DNA repair, cell cycle regulation, metastasis, and apoptosis. However, data showing the role of SPOCK1 role in pancreatic cancer tumorigenesis and progression are limited, and the mechanism underlying the differential expression of SPOCK1 is very unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SPOCK1 is an extracellular matrix glycoprotein, which is regarded as a candidate oncogene, has been verified to be closely related to the tumorigenesis, tumor progression, adhesion and metastasis of various tumors (36,37). Chen et al…”
Section: Discussionmentioning
confidence: 99%